06 Keeping the beat: does music improve the performance of chest compression by lay persons?. Issue 3 (1st March 2011) - Rawlins, Lettie; Woollard, Malcolm; Hallam, Phil; Williams, Julia
Abstract : Background: Early bystander cardiopulmonary resuscitation (CPR) increases survival from out-of-hospital cardiac arrest. Simplifying training can improve skill retention and confidence. A recent pilot study suggested music may help health professionals perform CPR. The song 'Nellie the Elephant' (tempo 100 bpm) is sometimes used to encourage compression rates in accordance with Resuscitation Council guidelines. This study investigates whether music helps lay persons perform compressions at 100 per minute. Methods: This randomised cross-over trial opportunistically recruited lay volunteers who performed three sequences, pre-randomised for order, of one minute of continuous chest compressions on a recording manikin accompanied by no music (NM) and repeated choruses of 'Nellie the Elephant' (Nellie), and 'That's The Way (I Like It)' (TTW). Results: Of 130 participants, 62% were male, median age was 21 (IQR 20 to 25), 72% had no previous CPR training. Mode and IQR for compression rate were NM 111 (93 to 119); Nellie 106 (98 to 107), (TTW) 109 (103 to 110). Within-groups differences were significant for Nellie vs NM and Nellie vs TTW (p<0.001) but not NM vs TTW (p=0.055). A compression rate of 95 to 105 was achieved with NM, Nellie, and TTW for 15/130 (12%), 42/130 (32%) and 12/130 (9%) attempts respectively. Differences in proportions were significant for Nellie vs. NM and Nellie vs TTW (p<0.0001) but not for NM vs TTW (p=0.55). Relative 'risk' for compression rate between 95 and 105 was 2.8 for Nellie vs NM (95%CI 1.66 to 4.80), 0.8 for TTW vs NM (95% CI 0.40 to 1.62), and 3.5 for Nellie vs. TTW (95% CI 1.97 to 6.33). Conclusion and recommendations: 'Listening to Nellie' (vs TTW or no music) significantly increased the proportion of lay persons achieving compression rates close to the 100 bpm guideline. Playing it during training and 'real' CPR may help rescuers deliver correct compression rates.